The Development and Implementation of a Multimedia Program that Uses Analogies in Senior High School Chemistry to Enhance Student Learning of Chemical Equilibrium - O'Brien, Geoffrey William (Curtin University, 2002)
In this thesis, you will find a review the development process of a multimedia presentation designed to assist the teaching of chemical equilibrium using analogies. The objective of this thesis is to report on the process of designing animated analogies and the subsequent employment of these analogies in a teaching program for grades 11 and 12 students. This thesis describes a case study in the effective use of technology in the classroom based on established research in the field of analogical thinking. The work begins with a review of relevant literature from the fields of constructivism, collaborative learning and multimedia in education. The design phase of the research sought to discover if analogies for chemical equilibrium could be successfully transferred to a multimedia presentation on a computer. The subsequent testing of the software endeavoured to discover the most appropriate teaching strategies and if the use of such a program could enhance the learning process for students. The work resulted in a completed CDROM with full teaching program included which you will find attached to this thesis. The results indicate that the experience was a positive one and that there is some evidence to show increased ability in the students in their attempts to understand a conceptually difficult area of chemistry theory.